How to „Read” a Dance Theatre Performance? - FELSEGHI, Alexandra (Studia Universitatis Babeș-Bolyai Dramatica, 2019)
The following article treats the subject of a dance theatre performance, by giving an inside and an outside perspective of the creative process. It also attempts to define the concept of dance dramaturgy and to explain the dramaturg’s function in the rehearsal room. On a level of perception, the audience’s function is a very important one, because the spectator becomes a co-author of the performer’s message. Therefore, the relationship between the stage and hall is a communication on different levels.